Agile Processes in Software Engineering and Extreme Programming 12th International Conference, XP 2011, Madrid, Spain, May 10-13, 2011. Proceedings - Sillitti, Alberto; Hazzan, Orit; Bache, Emily; Albaladejo, Xavier (Springer eBooks., 2011)
This book contains the refereed proceedings of the 12th International Conference on Agile Software Development, XP 2011, held in Madrid, Spain, in May 2011. The year 2011 marked the 10th anniversary of the Agile Manifesto. In this spirit, the XP conference continued its fine tradition of promoting agility by disseminating new research results in a timely manner and by bringing together researchers and practitioners for a fruitful mutual exchange of experiences. As introduced for XP 2010, there were again two different program committees, one for research papers and one for experience reports. Regarding the research papers, 11 out of 56 submissions were accepted as full papers; and as far as the experience reports were concerned, the respective number was 4 out of 17 submissions. In addition to these papers, this volume also includes the short research papers, the abstracts of the posters, the position papers of the PhD symposium, and the abstracts of the workshops.